Performance optimization of continuous countercurrent tangential chromatography for antibody capture. (17th March 2016) - Dutta, Amit K.; Tan, Jasmine; Napadensky, Boris; Zydney, Andrew L.; Shinkazh, Oleg
Abstract : Recent studies have demonstrated that continuous countercurrent tangential chromatography (CCTC) can effectively purify monoclonal antibodies from clarified cell culture fluid. CCTC has the potential to overcome many of the limitations of conventional packed bed protein A chromatography. This paper explores the optimization of CCTC in terms of product yield, impurity removal, overall productivity, and buffer usage. Modeling was based on data from bench‐scale process development and CCTC experiments for protein A capture of two clarified Chinese Hamster Ovary cell culture feedstocks containing monoclonal antibodies provided by industrial partners. The impact of resin binding capacity and kinetics, as well as staging strategy and buffer recycling, was assessed. It was found that optimal staging in the binding step provides better yield and increases overall system productivity by 8–16%. Utilization of higher number of stages in the wash and elution steps can lead to significant decreases in buffer usage (∼40% reduction) as well as increased removal of impurities (∼2 log greater removal). Further reductions in buffer usage can be obtained by recycling of buffer in the wash and regeneration steps (∼35%). Preliminary results with smaller particle size resins show that the productivity of the CCTC system can be increased by 2.5‐fold up to 190 g of mAb/L of resin/hr due to the reduction in mass transfer limitations in the binding step. These results provide a solid framework for designing and optimizing CCTC technology for capture applications. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:430–439, 2016